Estimation of the nonlinear dependence of the indications of a fiber Bragg grating on temperature and strain from experimental data (Fracture and Structural Integrity, 2022)
The readings of the Bragg grating are determined based on the optical radiation reflected from it. A quantitative characteristic of this radiation is the wavelength at which the maximum power of the optical signal is achieved. This characteristic is called the central wavelength of the grating. The central wavelength shift depends on temperature and strain. As a rule, a linear approximation of this dependence is used. However, from the available literature it is known that, the grating wavelength shift demonstrates a strong nonlinear dependence on temperature at 5
Keywords: Fiber Bragg grating; Calibration; Temperature compensation; Quadratic approximation